L’opéra, miroir des sociétés européennes - Clémence Schupp (Genre, Sexualité et Société)
Operas are written by social individuals having absorbed the norms of the society they live in. By working on a libretto, composers not only show their interest in a certain topic but also reflect the concerns of their time. During the first half of the 20th century a discussion about the traditional norms of gender and sexuality evolved in the West. Are the compositions of the composers, designated as the “moderns”, influenced by this discussion? The analysis of four representative librettos of this time gives, above all, an insight into the open-mind of some composers for liberal ideas. Additionally, the analysis also demonstrates how the creation of opera is influenced by the different ways of thinking of the time in the European societies. Modern opera both reflects the fear of a social progress in favour of women and homosexuals as well as the hope of establishing a liberal society.